PERUBAHAN STRUKTUR PATI GARUT (Maranta arundinaceae) SEBAGAI AKIBAT MODIFIKASI HIDROLISIS ASAM, PEMOTONGAN TITIK PERCABANGAN DAN SIKLUS PEMANASAN-PENDINGINAN [Structure Changes of Arrowroot (Maranta arundinaceae) Starch as Influenced b - Didah Nur Faridah; Dedi Fardiaz; Nuri Andarwulan; Titi Candra Sunarti (Jurnal Teknologi dan Industri Pangan, 2010)
The effects of lintnerization (2.2 N HCl, 2 hours), debranching with pullulanase (1.3 U/g and 10.4 U/g starch) and/or three-auctoclaving-cooling cycles at 121oC for 15 minutes on the changes of arrowroot starch structures were studied. The structural modifications of amylose and amylopectin were measured by Gel Permiation Chromatography (GPC), and the distribution of degree of polimerization (DP) was analyzed by Fluorophore-Assisted Capillary Electrophoresis (FACE). The GPC profile of native starch using Toyopearl HW-65S gel gave mainly two fractions. Fraction I (Fr. I) was a high molecular weight component and Fraction II (Fr. II) was a low molecular weight component. After acid modification, the carbohydrate content of Fr. II increased while that of Fr. I decreased. The amount of  DP of 6 to 8 increased in all modified arrowroot starches. The GPC and FACE analyses showed that all starch modification techniques caused the structural changes of amylopectin molecules to form short chain amyloses.